2023
DOI: 10.1038/s43247-023-00691-y
|View full text |Cite
|
Sign up to set email alerts
|

Higher concentrations of microplastics in runoff from biosolid-amended croplands than manure-amended croplands

Abstract: Land-applied municipal biosolids, produced from municipal wastewater treatment sludge, contributes to microplastics contamination in agroecosystems. The impacts of biosolids on microplastic concentrations in agricultural soil have been previously investigated, however, the potential for microplastics transport from biosolid-amended croplands has not been previously quantified. In this study, manure and biosolids were applied to field plots, runoff was collected following natural precipitation events and the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Beni et al reported higher concentrations of MPs in the runoff from croplands utilizing municipality sludge compared to croplands utilizing cattle manure as sources of fertilizer. Fibers and fragments were the most detected; however, films, foam, and beads were also observed [92]. Ross et al estimated that separate urban runoff outlets released between 1.9 million to 9.6 billion MPs every rain event to receiving water bodies [93], confirming that water runoff is a major pathway for transporting MNPs from land to aquatic environments (Figure 2).…”
Section: Mnps From Water Runoffmentioning
confidence: 97%
“…Beni et al reported higher concentrations of MPs in the runoff from croplands utilizing municipality sludge compared to croplands utilizing cattle manure as sources of fertilizer. Fibers and fragments were the most detected; however, films, foam, and beads were also observed [92]. Ross et al estimated that separate urban runoff outlets released between 1.9 million to 9.6 billion MPs every rain event to receiving water bodies [93], confirming that water runoff is a major pathway for transporting MNPs from land to aquatic environments (Figure 2).…”
Section: Mnps From Water Runoffmentioning
confidence: 97%
“…Spiked microplastics did not decant and instead adhered to the walls of the vessel, and settled particulate matter transferred into the filtering apparatus. An alternative method of separating the supernatant is centrifuging the digested solids with a high-density saturated salt solution to compact the solids into a pellet to aid in decanting the supernatant [ 3 , 12 , 16 , [18] , [19] , [20] ]. Centrifuging of samples may further fragment or compact microplastics into the solids pellet reducing recovery efficiency [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable shape category should, furthermore, be unambiguous and precise in describing a particle’s geometry. Commonly used shapes such as fiber , fragment , flake , pellet , bead , and foam are illustrative but not always well defined. , Still, many studies apply shape classes without clear geometric definitions, for instance, what characteristics define a fragment or a foam ? , Even with a clear definition, some shapes are only suitable for visual identification but not hyperspectral imaged microplastics, for instance, film. While unambiguous and precise geometric shapes can readily be defined, e.g., sphere , rectangle , and oval , it can be difficult to assign them to real microplastics as these can be of any shape.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 Still, many studies apply shape classes without clear geometric definitions, for instance, what characteristics define a fragment or a foam ? 5 , 22 Even with a clear definition, some shapes are only suitable for visual identification but not hyperspectral imaged microplastics, for instance, film. ( 20 ) While unambiguous and precise geometric shapes can readily be defined, e.g., sphere , rectangle , and oval , it can be difficult to assign them to real microplastics as these can be of any shape.…”
Section: Introductionmentioning
confidence: 99%